Impact of arsenic trioxide in the treatment of acute promyelocytic leukemia - Lengfelder, Eva; Hofmann, Wolf-Karsten; Nowak, Daniel (Leukemia, 2012)
Arsenic trioxide (ATO) is presently the most active single agent in the treatment of acute promyelocytic leukemia (APL). This review provides insights into the mode of action and the pharmacological properties of ATO, and summarizes the most relevant results of more than 20 treatment studies in relapsed or newly diagnosed APL published between 1997 and 2011. ATO acts by targeting multiple pathways in APL leading to apoptosis and myeloid differentiation. It induces complete remission without myelosuppression and causes only few adverse effects. In relapsed APL, ATO-based salvage therapy has been able to induce long-lasting remissions and possible cure in 50–81% of patients. In newly diagnosed APL, two main strategies are currently pursued. ATO is either included into induction therapy with the aim to minimize or eliminate chemotherapy, or it is incorporated as an additive into established first-line concepts with all-trans-retinoic acid and chemotherapy to reinforce their anti-leukemic efficacy. Recent results suggest a high efficacy of ATO in both concepts. In conclusion, experimental research and clinical studies have made contributions toward a better understanding of the molecular mechanisms induced by ATO in APL cells and have established this historic substance as an important candidate for the further improvement of APL therapy.